FISH-RICE FARMING AREA AT MANIK RAMBUNG RICE FIELD SUPPORTED FOOD SECURITY IN NORTHERN SUMATRA```` - Ameilia Zuliyanti Siregar (Talenta Publisher, 2015)
Rice and fish have been an essential part of the life of Indonesian people which produce from rice field. The research was conducted during two years (Dec.2008 to Sept.2010) using a purposive random sampling using three plots in lowland and terrace from Manik Rambung Rice Field (MRRF). Two types of rice crops (Ciherang and IR 64) are cultivated showed 6 orders, 21 families, 34 taxa and 25 species. Oligochaeta, Ephemeroptera, Hemiptera, and Diptera were identified respective families, while families of Odonata and Coleoptera were further identified to species. There are three categories of Dominance Index (DI) in a rice field, these are D=Dominant ( 5% individual); A=Accessory (2.5%  D  5% individual) and O=Occasional (2.5% individual) with four families (Baetidae, Chironomidae, Tubificidae and Ceratopogonidae) as ranked high on the DI list. The Kruskal-Wallis test showed significant differences between the abundance of aquatic organisms during the time of sampling (χ2=1274.840, P=0.000), rice-growing seasons (χ2=16.393, P=0.001) and rice cultivation phases (χ2=8.618, df=4, P=0.004). The study about fish farming produce plant and animal proteins and sustainable for food security in Northern Sumatra.